OS DESAFIOS E PERSPECTIVAS DO DIREITO SOBRE A ÓTICA DAS POLÍTICAS PÚBLICAS EM DEFESA DO PANTANAL - SOUZA, Ulysses Alves Cabral Cavalcante; PINHEIRO, Marina Ferreira Soares; SILVA, Guilherme Pinheiro (ANAIS DO ENIC, 2024)
-